Plasma miRNA can detect colorectal cancer, but how early?. (23rd March 2018) - Wikberg, Maria L.; Myte, Robin; Palmqvist, Richard; van Guelpen, Bethany; Ljuslinder, Ingrid
Abstract: Colorectal cancer (CRC) is a major cause of deaths worldwide but has a good prognosis if detected early. The need for efficient, preferable non‐ or minimally invasive, inexpensive screening tools is therefore critical. We analyzed 12 miRNAs in pre‐ and postdiagnostic plasma samples to evaluate their potential as CRC screening markers. We used a unique study design with two overlapping cohorts, allowing analysis of pre‐ and postdiagnostic samples from 58 patients with CRC and matched healthy controls. Plasma concentrations of miR‐15b, ‐16, ‐18a, ‐19a, 21, ‐22, ‐25, ‐26a, ‐29c, ‐142‐5p, ‐150, and ‐192 were measured by semi‐quantitative real‐time PCR. Concentrations of miR‐18a, ‐21, ‐22, and ‐25 in plasma from patients with CRC were significantly altered compared to healthy controls. Combined as a multimarker panel, they detected CRC with an AUC of 0.93. Furthermore, levels of these three miRNAs also showed different levels in the prediagnostic case samples close to diagnosis. Only miR‐21‐levels were elevated several years before diagnosis. Plasma levels of miR‐18a, ‐21, ‐22, and ‐25 show promise as screening biomarkers for CRC. However, based on our unique analysis of prediagnostic and postdiagnostic samples from the same patients, we conclude that circulating miRNAs elevated at diagnosis may not automatically be suitable for CRC screening, if the increase occurs too close to clinical diagnosis. Abstract : Increased plasma levels of miR18a, ‐21, ‐22, and ‐25 significantly identified patients with CRC, and when combined as a multimarker panel detected both early and late CRC stages with high sensitivity and specificity. Blood levels of miRNAs can detect both early‐ and late‐ stage CRC, and our data suggest potential usefulness in a prediagnostic screening setting. Prediagnostic samples can contribute important information in the design of optimal miRNA panels for clinical use.